Telecommunications markets in the stranglehold of EU regulation: on the need for a disaggregated regulatory contract - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2005)
The increasing complexity of EU regulation is resulting in a tangle of contradictory decisions and statements, involving also new markets, such as interactive cable television, Internet etc. Whereas in the past sector-specific regulation has been applied in a discretionary manner in order to correct the rules of the market game, the really challenging task for the future seems to be the development and implementation of statu- tory constraints for the regulatory authorities in order to guarantee a predictable regulation of market power. For this purpose the design and implementation of a disaggre- gated regulatory contract on the statutory level (EU Directives and national law) is derived, which should be an essential principle in the EU Review 2006. Its basic components consist of limiting regulation to monopolistic bottlenecks, exploiting the phasingout potentials, and a disaggregated application of regulatory instruments. In con- trast, the problem of opportunistic regulatory behaviour with respect to irreversible investments can be solved by the application of the already existing statutory constraint of the Framework Directive guaranteeing financial viability.
Keywords: 330; Telekommunikationspolitik; Wettbewerb; EU-Recht; EU-Staaten